PENGEMBANGAN PEDOMAN KULIAH KERJA LAPANGAN (KKL) BERBASIS KONTEKSTUAL DI PROGRAM STUDI PENDIDIKAN SEJARAH - Juniardi, Karel; Marjito, Emusti Rivasintha (Smart Education, 2025)
Abstract: This research aims to develop contextual-based Field Work Lecture (KKL) guidelines for students in the History Education Study Program at Universitas PGRI Pontianak. The main problem encountered in previous KKL implementations was the lack of guidelines tailored to local contextual needs, particularly in the application of learning based on the local environment and socio-cultural context. This research employed a Research and Development (R&D) method with a modified Borg & Gall development model consisting of six stages: needs analysis, planning, initial product development, limited trials, product revision, and field trials. The results indicate that these contextual-based KKL guidelines effectively improve students' ability to identify local potential, design KKL activities appropriate to the local socio-cultural context, and strengthen their reflective and collaborative skills. Expert validation indicated a